Richmond Pearson Hobson papers - Hobson, Richmond Pearson, 1870-1937.
Correspondence, memoranda, speeches, lectures, articles, reports, notes, analyses, orders, press clippings, photographs, and other papers relating chiefly to Hobson's naval career and to his efforts on behalf of prohibition, restrictions on international drug trafficking, and opposition to the Franklin D. Roosevelt administration. Documents Hobson's service during the Spanish-American War primarily pertaining to operations in Cuba and the Philippines; survey of Chinese, and Japanese, and British colonial navy-yards; proficiency in naval design and construction; and years as student and educator at the United States Naval Academy. Subjects include his advocacy of the enlargement of the U.S. Navy, a permanent fleet in the Pacific, and increase in the number of battleships; opposition to Franklin D. Roosevelt's expansion of the Supreme Court; Hobson's predictions of global conflict prior to both world wars; women's suffrage; sinking of the Lusitania; and industrial recovery during the Depression. Organizations represented include the Alcohol Education Society of America, Anti-saloon League of America, Constitutional Democracy Association, International Narcotic Education Association, Public Welfare Association, Woman's Christian Temperance Union, and World Narcotic Defense Association. Correspondents include and Pascual Cervera y Topete, French Ensor Chadwick, Theodore Roosevelt, Nikola Tesla, and Hobson's wife, Grizelda Hull Hobson, and other family members.
Library of Congress Rare Book and Special Collections Division.
Naval officer and U.S. representative from Alabama.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Cervera y Topete, Pascual, -- 1839-1909 -- Correspondence; Chadwick, French Ensor, -- 1844-1919 -- Correspondence; Hobson, Grizelda Hull -- Correspondence; Roosevelt, Franklin D. -- 1882-1945.; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Tesla, Nikola, -- 1856-1943 -- Correspondence; Hobson family -- Correspondence; United States. -- National Prohibition Act; United States. -- Navy -- Equipment; United States. -- Navy. -- Pacific Fleet; United States. -- Supreme Court; Alcohol Education Society of America; American Public Welfare Association; Anti-saloon League of America; Constitutional Democracy Association; International Narcotic Education Association; Public Welfare Association; Lusitania (Steamship); United States Naval Academy; Woman's Christian Temperance Union; World Narcotic Defense Association; Battleships -- United States; Depressions -- 1929 -- United States; Drug traffic; Narcotics; Naval architecture; Navy-yards and naval stations -- China; Navy-yards and naval stations -- Great Britain; Navy-yards and naval stations -- Japan; Prohibition -- United States; Shipbuilding; Spanish-American War, 1898 -- Naval operations -- Cuba; Spanish-American War, 1898 -- Naval operations -- Philippines; Temperance -- United States -- Societies, etc; Women -- Suffrage -- United States; World War, 1914-1918 -- Prophecies; World War, 1939-1945 -- Prophecies; United States -- Economic conditions -- 1918-1945.; United States -- History, Naval; United States -- Politics and government -- 1933-1945.; Naval officers; Representatives, U.S. Congress -- Alabama